Food and wealth from the seas: health check for the marine fisheries of Malaysia - Tai, Shzee Yew (Universiti Putra Malaysia Press, 2014)
From the bio-economic perspectives, the state of health of the Malaysian marine fisheries is far from satisfactory. Studies have shown that almost all fish stocks are either fully or overexploited due to excessive fishing effort and fleet overcapacity applied to these stocks, resulting in the dissipation of millions Malaysian Ringgits of resource rent. Thus the marine fisheries sector is an under-performing natural asset. In order to reverse the situation and to restore the full potential of the sector that will be able to contribute to the economic growth and social development of Malaysia, marine fisheries management reform is suggested. Fisheries reform is a complex, arduous and long process that requires political will and institutional supports. Successful fisheries management reform requires adaptively creating and continually adjusting a sound management plan or “road map”. It entails rebuilding of the depleted fish stocks through the establishment of artificial habitats such as artificial reefs and marine protected areas, the curtailment of excessive fishing effort and fishing capacity and the stamping out of the illegal fishing as well as the unregulated and unreported catches. The rebuilt fish stocks will improve productivity, increase sustainable yields, lower fishing costs, increase profitability and economic benefits. The success of fisheries reform also entails the management of the political and economic processes. It requires changing the marine tenure structure from the “common pool” that promotes competition to one such as co-management that delegates exclusive and secures user-rights to the fishers’ communities that encourages cooperation in management and responsibilities among stakeholders. The success of fisheries reform requires building consensus on common visions among stakeholders and consequently gaining their confidence as well as support for the reform agenda. These need to be based on the dissemination of information generated from scientific research to raise awareness among leaders, stakeholders and the public of the need to undertake fisheries management reforms. Successful fisheries reform needs to safeguard social equity through transparent equitable sharing of benefits. Social equity also requires providing social safety nets and creating alternative employment and economic opportunities for affected and displaced fishers. The pernicious fishing input subsidies need to be restructured, rationalized and gradually removed as they provide the economic incentive to continue fishing even though it is unprofitable.